2017
DOI: 10.1590/1982-43272767201708
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Organizational Values on Quality of Work Life

Abstract: Quality of work life (QWL) is a topic studied globally due to its relevance for workers’ health and organizational results. This study investigated the effects of person-organization fit (POF) with regard to workers’ perceived and desired organizational values (OV) on QWL. The sample consisted of 213 Brazilians working in companies of different sizes and from different sectors. The quadratic polynomial regression model with surface analysis charts was used. The hypothesis that QWL is affected by satisfaction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
(23 reference statements)
0
4
0
1
Order By: Relevance
“…Therefore, having a good quality of life at work means performing one's functions while valuing well-being and mental and physical health [78]. A QWL program aims to improve work practices to achieve results with adequate working conditions and social integration [79]. For [80], QWL is an opportunity to redesign the nature of work, focusing on workers' quality of life and improving productivity for the organization.…”
Section: Theoretical Framework and Study Hypothesesmentioning
confidence: 99%
“…Therefore, having a good quality of life at work means performing one's functions while valuing well-being and mental and physical health [78]. A QWL program aims to improve work practices to achieve results with adequate working conditions and social integration [79]. For [80], QWL is an opportunity to redesign the nature of work, focusing on workers' quality of life and improving productivity for the organization.…”
Section: Theoretical Framework and Study Hypothesesmentioning
confidence: 99%
“…Levando em consideração que o contexto de trabalho (2,87±0,52) dos professores mostrou resultados críticos nas condições de trabalho (3,14±0,74) e organização do trabalho (3,37±0,56), é importante destacar que os valores organizacionais, no ambiente de trabalho, influenciam na qualidade de vida dos trabalhadores Rueda, 2017). Apesar da qualidade de vida dos professores está com indicadores positivos, é importante que haja alteração deste cenário como pressuposto para evitar o agravamento da situação.…”
Section: Métodounclassified
“…Studies have shown that 46% of potential employees cite organizational values and culture as important when choosing the organization to work in, while 88% of potential employees cite organizational values and culture as of relative importance during job seeking as key to business success [39]. Employees who don't like their organization's culture and values are 24% more likely to quit while 15% of job seekers instantly turned down a job offer because of the organization's values, ethics, and culture [21]. 43% of workers say they left their organization because of career path constraints, while 63% of employees say they would not consider a job if the organization offered fewer than 15 days of pay time off each year, while 57% of workers are more loyal, productive and take less time off when employers support their mental well-being.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Organizational culture such as flexible working hours, strong team dynamics, and clear goals to work towards, determine even the choice of organization the employees would want to work in [44], [47], [66], and [68]. Organizational behavior, values, and culture can affect the way people make decisions for or against the organization [21] and [41]. Businesses that are able to encourage risks in decision-making within the organization's culture can enhance innovation and creativity.…”
Section: Introductionmentioning
confidence: 99%